Emeriti Professors as entrepreneurs - Raymond Saner (Public Administration and Policy)
Purpose – This study explores the roles and opportunities for Emeriti Professors in contributing to academia and society post-retirement. Design/methodology/approach – This study utilizes a comparative analysis of retirement policies across internationally active universities. The research investigates motivations for continued work and the impact of emeritus status on academic engagement. ChatGPT was used to create Tables 1 and 2. Findings – Based on the literature review, media reports, published data on university websites, webinar insights, and personal interviews, the findings reveal diverse post-retirement activities and highlight the potential of Emeriti Professors to support the 2030 Agenda for Sustainable Development. Originality/value – This study underscores the importance of institutional support to leverage the expertise of retired faculty in addressing global challenges.